Penguatan Literasi Digital untuk Pemasaran Produk Ekonomi Sirkular sebagai Pendekatan Pembangunan Inklusif yang Mendukung Program Pemerintah Kota Jambi di Kelurahan Eka Jaya - Maulana, Rio Yusri; Subekti, Dimas; Darminto, Citra; Sazeta, Mirza; Asiah, Uswatun (Universitas Pahlawan Tuanku Tambusai, 2026)
The urgency of this community service is the importance of strengthening digital literacy for marketing circular economy products as an inclusive development approach that supports the Jambi City government's program in Eka Jaya Village. The methods used include training, direct mentoring, participatory observation, and evaluation of results through pre- and post-activity surveys. The results of the activity show a significant improvement in the participants' digital skills. Integrating activities with the happy village Program fosters positive synergy among the community, academics, and local government in achieving a digital-based, inclusive economy. From a social impact perspective, this activity successfully formed a collaborative network among MSME actors, youth groups, and housewives in developing environmentally friendly businesses with circular economic value. Besides this activity, it also strengthens awareness of the importance of household waste management and environmental conservation. Thus, strengthening digital literacy for marketing circular economy products not only contributes to the economic independence of the community but also becomes part of a sustainable and inclusive development strategy that aligns with the Jambi City Government's vision of a productive, intelligent, and sustainable happy village.